Afatinib versus methotrexate as second-line treatment in Asian patients with recurrent or metastatic squamous cell carcinoma of the head and neck progressing on or after platinum-based therapy (LUX-Head & Neck 3): an open-label, randomised phase III trial. (10th September 2019) - Guo, Y; Ahn, M -J; Chan, A; Wang, C -H; Kang, J -H; Kim, S -B; Bello, M; Arora, R S; Zhang, Q; He, X; Li, P; Dechaphunkul, A; et al.
Abstract: Background: Treatment options are limited for patients with recurrent or metastatic squamous cell carcinoma of the head and neck (HNSCC) following progression after first-line platinum-based therapy, particularly in Asian countries. Patients and methods: In this randomised, open-label, phase III trial, we enrolled Asian patients aged ≥18 years, with histologically or cytologically confirmed recurrent/metastatic HNSCC following first-line platinum-based therapy who were not amenable for salvage surgery or radiotherapy, and had an Eastern Cooperative Oncology Group (ECOG) performance status of 0/1. Patients were randomised (2 : 1) to receive oral afatinib (40 mg/day) or intravenous methotrexate (40 mg/m 2 /week), stratified by ECOG performance status and prior EGFR-targeted antibody therapy. The primary end point was progression-free survival (PFS) assessed by an independent central review committee blinded to treatment allocation. Results: A total of 340 patients were randomised (228 afatinib; 112 methotrexate). After a median follow-up of 6.4 months, afatinib significantly decreased the risk of progression/death by 37% versus methotrexate (hazard ratio 0.63; 95% confidence interval 0.48–0.82; P = 0.0005; median 2.9 versus 2.6 months; landmark analysis at 12 and 24 weeks, 58% versus 41%, 21% versus 9%). Improved PFS was complemented by quality of life benefits. Objective response rate was 28% with afatinib and 13% with methotrexate. There was no significant difference in overall survival. The most common grade ≥3 drug-related adverse events were rash/acne (4% with afatinib versus 0% with methotrexate), diarrhoea (4% versus 0%), fatigue (1% versus 5%), anaemia (<1% versus 5%) and leukopenia (0% versus 5%). Conclusions: Consistent with the phase III LUX-Head & Neck 1 trial, afatinib significantly improved PFS versus methotrexate, with a manageable safety profile. These results demonstrate the efficacy and feasibility of afatinib as a second-line treatment option for certain patients with recurrent or metastatic HNSCC. Clinical trial registration: ClinicalTrials.gov identifier: NCT01856478.